S43 Mortality following surgical lung biopsy for the diagnosis of interstitial lung disease in the United States: 2000–2011. (12th November 2015) - Hutchinson, JP; McKeever, TM; Fogarty, AW; Hubbard, RB
Abstract : Introduction: Surgical lung biopsy can help to achieve a specific diagnosis in interstitial lung disease, but has associated risks. Most currently available mortality data come from case series. Objective: We aimed to assess in-hospital mortality following surgical lung biopsy for interstitial lung disease in a national secondary care dataset. Methods: Data were obtained from the Nationwide Inpatient Sample, an anonymised yearly sample of US community hospitals developed for the Healthcare Cost and Utilisation Project (HCUP). We identified cases from 2000–2011 using International Classification of Diseases (ICD-9-CM) codes for interstitial lung disease, and procedure codes for surgical lung biopsies. Lung resections and cases of lung cancer were excluded. We estimated numbers of biopsies nationwide and in-hospital mortality, and used multivariate logistic regression to assess risk factors for mortality, adjusting for sex, age, geographic region, co-morbidity, type of operation, and provisional diagnosis. Results: We estimated there to be around 12, 000 surgical lung biopsies performed annually for interstitial lung disease in the United States, two-thirds of which were performed electively. In-hospital mortality was 1.7% for elective procedures, but significantly higher for non-elective procedures (16.0%). Male sex, increasing age, increasing co-morbidity, open surgery and a provisional diagnosis of idiopathic pulmonary fibrosis or connective tissue disease related interstitial lung disease were risk factors for increased mortality. Conclusions: In-hospital mortality following elective surgical lung biopsy for interstitial lung disease is just under 2%, but significantly higher for unplanned procedures. The mortality risk and risk factors for death should be taken into account when counselling patients on whether to pursue a histological diagnosis.